Pathways from parental trauma exposure to Syrian and Iraqi refugee youth mental health symptoms: a multi-level mediation analysis - Shirley ElFishawy; Liza Hinchey; Rachel Morrison; Mahmood Sanad; Arash Javanbakht (BMC Public Health)
Abstract Background Trauma experienced by one generation has potential to impact those that follow. Refugee youth in particular are vulnerable to trauma and its intergenerational effects. By examining trauma subtypes, the impact of parental trauma, and post-/pre-migration stressors, this study investigated pathways linking parental trauma to psychological symptoms in Syrian and Iraqi refugee youth. Methods Participants included 165 minors from Syria and Iraq, and their 107 parents (56 mothers, 51 fathers), all of whom experienced forced migration due to war and resettled as refugees in southeast Michigan. Linear mixed-effects modeling and multi-level mediation analyses were employed to investigate pathways from parental trauma exposure to child symptoms (anxiety, depressive, and somatic), as well as possible explanatory mediators. Results Maternal cumulative trauma and death threat trauma were associated with child depressive symptoms (cumulative: b = 1.64, p =.007; death threat: b = 2.70, p =.020) and somatic burden (cumulative: b = 0.56, p =.032; death threat: b = 1.04, p =.041). Anxiety models also revealed an association between maternal cumulative trauma and child anxiety (b = 1.79, p =.034). Maternal post-migration living difficulties fully mediated the observed association between maternal cumulative trauma and child depression, though this effect was trending in sensitivity analyses. No paternal trauma variables were associated with child symptoms. Conclusion Findings indicate that maternal trauma exposure in particular—as well as elevated post-migration stressors for mothers—may contribute to mental health risk in refugee youth. These insights may be leveraged towards early identification of youth at high risk, and to direct focused intervention towards modifiable targets—including living difficulties (e.g., financial difficulties, access to health care and transportation) experienced by parents post-migration. Clinical trial number Not applicable.